Trends and challenges in sport science and engineering related technology education at surf science and technology: Researching surfboard making activity - Audy, J. (International Journal of Sports Science and Engineering, 2007)
The paper presents the results obtained from teaching, learning and research associated with Surf Science and Technology (SST) course taught at the South West Campus of Edith Cowan University. The main topic discussed is Teaching and Learning with the Surfboard Making. It looks at a group of recent second year SST students who, after acquiring the necessary scientific and technological skills related to the production and performance of surfboards, were asked to design and produce their own surfboard during the Surf Equipment, Design, Materials and Construction Course. The first part of this paper describes briefly the most important steps in the surfboard making procedure. It is then followed by a series of photographs showing the SST students in various surfboard shaping and laminating activities. The next section provides some examples from teacher-student interactions in terms of individual approach and the group as a whole. It was realized that each student aimed to create a surfboard that would best suit his or her surfing skill. This resulted in the production of various surfboards that differed in the length, shape, weight, appearance, the number of fins, fin design and the surfboard/fin material. The results were analysed using a comparative statistical method that allowed determining the relative importance of each qualitative criterion with respect to other criteria associated with surfboard design features and performance. Following the discussion of the results, there are main conclusions highlighting the outcomes interesting from both pedagogical and professional practice perspectives.